Struktur Frase dan Transformasi Bahasa Pada Puisi Aku Karya Chairil Anwar - Yustina Sako; Antonius Bere (STIKes Ibnu Sina Ajibarang, 2023)
Phrase structure and transformation is a theory of generative transformation grammar which can produce or generate and change a certain linguistic form into another new linguistic form, which did not previously exist. Language consists of a deep layer and a surface layer. This theory separates language into two layers, namely deep structure and surface structure. Language analysis always starts from the sentences in the poem